정상, 고안압증, 녹내장 의증, 녹내장안에서 매트릭스 시야계와 험프리 표준 자동 시야계간의 결과 비교 - 천현철; Hyun Chul Cheon; 정우진; Woo Jin Jeung; 노세현; Sae Heun Rho (Daihan angwa haghoi jabji, 2007)
목적 : 험프리 매트릭스 시야계와 험프리 표준 자동 시야계의 검사 결과 상관성과 험프리 매트릭스 시야계의 임상적 유용성을 알아보고자 하였다. 대상과 방법 : 전체 170명 환자의 170안을 대상으로 하였으며, 정상 50안, 고안압증 20안, 녹내장 의증 50안, 녹내장 50안으로 세분하였다. 각각의 대상안은 험프리 표준 자동 시야계와 험프리 매트릭스 시야계 검사를 시행하였으며, 각 군별로 그 결과를 비교 분석하였다. 결과 : 정상안 군을 제외한 고안압증, 녹내장 의증, 녹내장 군에서 두 시야계 결과가 통계적으로 유의한 상관관계를 보였다. 결론 : 험프리 매트릭스 시야계는 험프리 표준 자동 시야계와 유사한 진단적 유용성을 가지며, 녹내장 조기진단에도 효과가 있을 것으로 생각된다. <한안지 48(5):678-685, 2007> Purpose: To study the correlation between the Humphrey standard automated perimetry (SAP) and the Humphrey Matrix Frequency Doubling Technology (FDT) perimetry and diagnostic usefulness of the Humphrey Matrix FDT perimetry. Methods: This study included 170 eyes of 170 patients. The 170 eyes were classified into 50 normal eyes, 20 ocular hypertensive eyes, 50 glaucoma-suspect eyes and 50 glaucomatous eyes. All subjects were examined with the Humphrey Matrix perimetry and the Humphrey standard automated perimetry. We studied the correlations between mean deviation (MD) and pattern standard deviation(PSD) of the Humphrey SAP and those of the Humphrey Matrix perimetry, respectively, in each of the classified group. Results: Overall, MD and PSD of the Humphrey SAP were significantly correlated with MD and PSD of the Humphrey Matrix perimetry, respectively. However, MD and PSD of the Humphrey Matrix perimetry were not showed a significant correlation in normal subjects (P>0.05). Conclusions: In this study, there were significant correlations between the MD and PSD of the SAP and those of the Humphrey Matrix perimetry in glaucoma, glaucoma-suspect and ocular hypertension. These finding suggests the Humphrey Matrix perimetry has performance characteristics similar to SAP and diagnostic value. J Korean Ophthalmol Soc 48(5):678-685, 2007